Correlation Craniofacial Growth, Body Height and Cervical Vertebrae Maturation Stages - Maria K. Ellyeus; Loes Sjahruddin; Widijanto Sudhana; Hamilah D. Koesoemahardja (Faculty of Dentistry, Universitas Indonesia, 2013)
Growth and development period has benefit for treating patient who need orthodontic treatment. In this period craniofacial development can be modified. Indicators that can be used to assess the growth and development among others are through body height and cervical vertebrae maturity stages (CMVS). Several previous studies have indicated that craniofacial growth is similar to body growth and there is gender difference between boys and girls. Objectives: Identifying correlation between craniofacial growth, body height and CVMS between gender in Deutero-Malay group aged 10-17 years old. Methods: A cross sectional study was conducted with samples of 159 subjects (72 males and 86 females). Craniofacial growth assessed in five dimensions (N-Me, S-Go, S-NA, PNS-A, Go-Pog). CVMS as described by Baccetti's method, body height was measured. Results: Pearson and Spearman's correlation coefficient revealed body height has stronger relationship with CVMS than craniofaial growth (r=0.838; p<0.05) (r=0.647; p<0.05). Correlation coefficient craniofacial height (Na-Me, S-Go) and mandibula length (Go-Pog) have stronger relationship with CVMS (r=0.458; r=0.465; r=0.545; respectively p<0.05) than the length of craniofacial (S-N, PNS-A) in boys and girls group (r=0.283; r=0.237; p<0.05). T-test revealed difference in body height (p<0.05) and craniofacial growth between boys and girls in group age 13-15 years old (p<0.05). Mann-Whitney test revealed differences in CVMS between males and females in age 10-17 years old (p<0.05). Conclusions: Body height, craniofacial height and mandibular length were correlated with CVMS.